Physicochemical Factors Affected the Partial Purified Lipase Activity of Acinetobacter baumannii â€œlocal isolatesâ€ - Huda J. Mohammed (College of Pharmacy University of Baghdad, 2017)
Microbial lipases today occupy a place of prominence among biocatalysts owing to their ability to catalyze awide variety of reactions in aqueous and non- aqueous media, A.baumannii were isolated from different clinical specimens from hospitalized patients from Baghdad hospitals and were detected by biochemical tests and API20E system. The percentage of isolation was (16.6%), A. baumannii is an increasingly multidrug â€" resistant (MDR), it showed high level of resistant to Ceftriaxon, Colistin, Piperacillin, Co-trimoxazol, Tertracycline, Carbenicillin, Amoxicillin, Penicillin G, Gentamicin and Ceftazidim , wherease the isolates were highly sensitive to Imipenem, Ciprofloxacin, Meropenem, Amikacin, and Cefotaxime. The isolated strians of A.baumannii were screened for the production of lipase by using Rhodamine B agar media. one of the isolated strians exhibited a greater clear zone than the others, indicated higher lipase activity.  The lipase in present study was partially purified by ammonium sulphate at the concenterations of 30% and 80%, the 30% ammonium sulphate showed higher activiy of the enzyme than 80% in which the enzyme activity was slightly decreased indicating that the better purification was at the 30% concenteration of ammonium sulphate.Various physicochemical parameters such as pH, temperature and metal ions were studied in order to determine the optimum conditions for lipase production. The production of lipase by A. baumannii was optimum at 35Â°C, pH 7.0 and was enhanced by the Ca++ and Na+ wherease inhibited by Zn++ ions. Key words : Acinetobacter baumannii, Lipase enzyme, Partial purification.